Estudio de factibilidad para la creación de la empresa “el huerto del Quindío” dedicada a la producción y comercialización de productos alimenticios verduras mixtas picadas en el municipio de Calarcá, Quindío. (2012)
Below is the research work carried out in the municipality of Calarcá Quindío, which allows to observe the current situation of the market in the locality and the acceptance of a food product such as chopped mixed vegetables, in order to carry out a feasibility study for the creation of the company "El Huerto del Quindío"